2021
DOI: 10.1021/acs.jafc.1c04852
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Thermostability and Catalytic Activity of an Inulosucrase by Rational Engineering for the Biosynthesis of Microbial Inulin

Abstract: Thermostability and enzymatic activity are two vital indexes determining the application of an enzyme on an industrial scale. A truncated inulosucrase, Laga-ISΔ138-702, from Lactobacillus gasseri showed high catalysis activity. To further enhance its thermostability and activity, multiple sequence alignment (MSA) and rational design based on the modeled structure were performed. Variants A446E, S482A, I614M, and A627S were identified with an improved denaturation temperature (T m) of more than 1 °C. A combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Consensus sequence design, a widely accepted approach to improving the thermostability of biocatalysts, , was performed using thermophilic proteins as align models to search for the hot spots that affect the Cp KR thermostability. The EnzymeMiner platform, a user-friendly bioinformatic tool, was employed to retrieve thermophilic enzymes sharing a certain degree of identity with Cp KR. , Using the sequence of Cp KR as a query and identifying Ser133, Tyr171, and Lys175 as the essential residues for catalysis and cofactor binding, four proteins from thermophiles were obtained (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consensus sequence design, a widely accepted approach to improving the thermostability of biocatalysts, , was performed using thermophilic proteins as align models to search for the hot spots that affect the Cp KR thermostability. The EnzymeMiner platform, a user-friendly bioinformatic tool, was employed to retrieve thermophilic enzymes sharing a certain degree of identity with Cp KR. , Using the sequence of Cp KR as a query and identifying Ser133, Tyr171, and Lys175 as the essential residues for catalysis and cofactor binding, four proteins from thermophiles were obtained (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Consensus sequence design, a widely accepted approach to improving the thermostability of biocatalysts, 40,41 was performed using thermophilic proteins as align models to search for the hot spots that affect the CpKR thermostability.…”
Section: Combination Of Stabilizing Mutations Identified Frommentioning
confidence: 99%
“…reuteri 121 (50 °C) and IS from L . gasseri (55 °C) [ 27 , 28 ]. To further test the stability of Psor-LS at different temperatures, the enzyme was incubated at 45, 55, and 65 °C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have confirmed that the catalytic properties can be further improved by combining mutation sites that affect the same catalytic property [ 32 , 49 ]. Since S33T, T174V, and N218L variants enhanced different catalytic properties of rAprY, we performed combinational mutagenesis to further improve the catalytic properties of rAprY.…”
Section: Resultsmentioning
confidence: 99%